2010
DOI: 10.1111/j.1365-2133.2010.09983.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional variability of the adenosine A3 receptor (ADORA3) gene polymorphism in aspirin-induced urticaria

Abstract: SummaryBackground To improve understanding of aspirin hypersensitivity, this study focused on adenosine as a noncyclooxygenase target molecule of aspirin. Adenosine may affect the release of histamine from cutaneous mast cells through a mechanism mediated by the adenosine A3 receptor. Objectives To investigate the genetic contribution of adenosine A3 receptor gene (ADORA3) polymorphisms in the pathogenesis of aspirin-induced urticaria (AIU) in a case-control association study in a Korean population. Methods A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Finally, further associations have been found with the adenosine receptor A3 gene (-1050G>T and -564C>T) [117], IL4 (-589T>C) [112,118], IL10 (-1082 G>A) [112], CTLA (49A>G) [112], nitric oxide synthase 2 [119], and the HLA system [120][121][122].…”
Section: Other Variants Outside Eicosanoid Biosynthesismentioning
confidence: 99%
“…Finally, further associations have been found with the adenosine receptor A3 gene (-1050G>T and -564C>T) [117], IL4 (-589T>C) [112,118], IL10 (-1082 G>A) [112], CTLA (49A>G) [112], nitric oxide synthase 2 [119], and the HLA system [120][121][122].…”
Section: Other Variants Outside Eicosanoid Biosynthesismentioning
confidence: 99%
“…Nevertheless, the missense polymorphism rs10156191 (Thr16Met) in diamine oxidase, which causes impaired metabolism of circulating histamine, was associated with NIUA, NERD, and a mixed reaction pattern [91]. Other genetic associations in NSAID-induced DHRs have been found with polymorphisms in the adenosine receptor A3 gene (ADORA3) (-1050G>T and -564C>T), IL4 (-589T>C) [90], IL13 (-1111C>T), and HLA [92][93][94][95][96]. We analyzed 9 SNPs in 5 genes involved in mast cell activation in NIUA and found statistically significant differences when patients were stratified according to clinical symptoms [97].…”
Section: Cross-intolerance To Nsaidsmentioning
confidence: 99%
“…3 Leukotriene overproduction may be one of the mechanisms responsible for AIU, 1,4 which is supported by genetic studies showing significant association of leukotriene C4 synthase (LTC4S) 5,6 and 5-lipoxygenase (ALOX5). 7 In addition, previous genetic association studies have reported that the IgE high affinity receptor (FCER1A), 8 histamine N-methyltransferase (HNMT) 9 and adenosine A3 receptor (ADORA3) 10 genes are genetic determinants of AIU, which indicates that genetic variation associated with increased histamine release and ⁄or augmented mast cell signalling, leading to the release of proinflammatory mediators, can contribute to the development of AIU.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by our previous research, which suggested that neutrophil activation may be involved in the pathogenesis of AIAU. 2,10,11 In this study, better to understand the role of IL-18 in the development of AIAU, we examined the effect of the high transcript haplotype, ht1 [CG], on neutrophil chemotaxis in peripheral blood neutrophils from patients with AIU. We found increased neutrophil chemotaxis in subjects exhibiting the high transcript haplotype ht1 [CG], and decreased neutrophil chemotaxis in those with the low transcript haplotype ht2 [AG].…”
Section: Discussionmentioning
confidence: 99%